Synthesis and Antimicrobial Activity of 4-S-Methyl-1,3,4-Oxadiazole Derivatives of Some Natural Amino Acids Bearing Secondary Quaternary Ammonium Salt Moieties - Sofiane, Daoudi (2018)
Secondary quaternary ammonium salts (QAS) derived from three natural amino acids (L-Leucine, L-Phenylalanine and L-Methionine) bearing 1,3,4-oxadiazole and acetic acid moieties have been synthesized and characterized by IR, 1H and 13C NMR. All the synthesized compounds were evaluated for their preliminary in vitro antibacterial and antifungal activity against different bacterial and fungal strains. All the synthesized compounds showed varying degrees of inhibition against the tested microorganisms. DOI: http://dx.doi.org/10.17807/orbital.v10i7.990